Pelaksanaan Pemberdayaan Masyarakat Melalui Program Keterampilan Hidup dan Wirausaha di PKBM Luthfillah Kelurahan Pahandut Kota Palangka Raya - Pahri Adi K (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2021)
Empowerment is a process of empowering communities where the community is given an ability to manage all available resources to improve the standard of living of the community itself. One form of empowerment is like what has been done in PKBM Lutfillah and has been running since 2007. The problems that will be discussed in this paper are about how to implement community empowerment through Life Skills and Entrepreneurship Programs in PKBM Luhtfillah Pahandut Urban Village, Palangka Raya City, and whatever supporting and inhibiting factors for the implementation of the Life and Entrepreneurship Skills Program at PKBM Lutfillah. The theory used in this study is using the theory of Edi Suharto (2011), namely: planned and collective activities; improve people's lives; priority for weak and disadvantaged groups; and carried out through capacity building programs. This type of research uses qualitative research methods where the purpose is to describe and analyze the implementation of Life and Entrepreneurship Skills Program in PKBM Luthfillah as well as supporting factors and inhibiting factors that influence the implementation of the program. Which in this study is data collection through observation, interview, and documentation techniques. The analysis technique is through data collection, data reduction, data presentation, and drawing conclusions and verification. The results showed that in the implementation of Life and Entrepreneurship Skills Program in PKBM Luthfillah through 3 stages, namely the recruitment of prospective participants, implementation, and closure had been going well and the benefits had really been felt by participants both to improve their thinking skills but also able improve their lives by creating a new independent business. in addition to increasing their economic income, they are also able to change their mindset so that they are more critical in fulfilling their needs by not always relying on government assistance. Supporting factors that influence the implementation of the program are; availability of tutors, availability of funds, and availability of facilities. While for the inhibiting factors is; capture power, and time constraints.